Corpus-based sociolinguistics : a guide for students - Friginal, Eric.; Hardy, Jack A. (New York : Routledge, 2014)
'In the last decade, the availability of corpora and the technological advancements of corpus analysis tools have increased dramatically. Applied linguistics and linguistics scholars have greater access to data from around the world and in a variety of languages through websites, blogs, and social networking sites, and there is a high level of interest among these scholars in applying corpora and corpus-based methods to other research areas, particularly sociolinguistics. This innovative guidebook presents a systematic, in-depth account of using corpora in sociolinguistic research. It introduces and expands the application of corpora and corpus approaches/tools in sociolinguistic research, surveys the growing number of studies in corpus-based sociolinguistics, and provides instructions and options in how to design and develop a corpus-based sociolinguistics study. Readers will find practical information on such contemporary topics as using the web as a corpus, megacorpora, and web registers. Vignettes, case studies, discussion questions, and activities throughout further enhance students' involvement of the material and provide opportunities for hands-on practice of the methods discussed. This complete and accessible guide to corpus-based sociolinguistics is a must-read for any student or scholar interested in exploring this popular and promising approach to sociolinguistic research'--
Includes bibliographical references : (pages 290-309) and index.
Keywords: Sociolinguistics